PENGARUH VISUAL THINGKING STRATEGY IN AUGMENTED REALITY DALAM MEMFASILITASI KETERAMPILAN PEMECAHAN MASALAH - M. Fauzan Abdillah; Saefullah, Asep; Guntara, Yudi (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
This study proposes the Visual Thinking Strategy in Augmented Reality (ViTSAR) application, which combines E-modules, LKPD, and interactive media. The approach used in this study is quantitative with a Pretest-Posttest Nonequivalent group design. The population used in this study were students of class XII MIPA. While the sample to be used in this study consisted of class XII MIPA 3 as the experimental class and XII MIPA 5 as the control class at SMAN 1 Baros. This study used a problem-solving skills test instrument in the form of a description and a student response questionnaire instrument. Data analysis was conducted using descriptive statistics T-test to determine the effect of ViTSAR learning media on the experimental and control classes. The results of the hypothesis test showed that the value of Tcount = 5,700 was greater than Tcount = 2,447, so there was a difference in the mastery of problem-solving skills of the experimental class and the control class on the Gauss law material.